Perception of the conception of compassion and wisdom: a study of university students - Ruiz Mendoza, Karla Karina (2023)
This paper analyzes the importance of compassion and wisdom in holistic education, for which the concepts learned by university students were reviewed. The justification for the topic is based on the need to form more humane and committed individuals to their environment. The objective was to review the theoretical framework around compassion and wisdom, as well as to analyze the results of a descriptive cross-sectional observational study conducted with essays from 12 students of the Bachelor's Degree in Psychopedagogical Counseling from a university in Mexico. The results showed that the essay is an essential didactic resource for learning compassion and wisdom, as it allows students to learn from themselves and their own reflections. In conclusion, the importance of including these values in the training of individuals committed to their environment is highlighted, and it is suggested that holistic education is an effective tool to achieve this.